Maximizing the use of aquifer thermal energy storage systems in urban areas: effects on individual system primary energy use and overall GHG emissions. (1st April 2022) - Beernink, Stijn; Bloemendal, Martin; Kleinlugtenbelt, Rob; Hartog, Niels
Highlights: The primary energy use of ATES systems evaluated for high and low aquifer utilisation levels. High aquifer utilisation levels reduce energy use of individual systems, as more wells can be placed. The highest aquifer utilization level considered is 115% and resulted in 82% ATES adoption. For aquifer utilization <80%, energy use of buildings is not affected by subsurface interactions. For aquifer utilization >80%, interactions affect gas use +15% and electricity use +/-15%. Abstract: Low temperature (<25 °C) Aquifer Thermal Energy Storage (ATES) systems have a world-wide potential to provide low-carbon space heating and cooling for buildings by using heat pumps combined with the seasonal subsurface storage and recovery of heated and cooled groundwater. ATES systems increasingly utilize aquifer space, decreasing the overall primary energy use for heating and cooling for an urban area. However, subsurface interaction may negatively affect the energy performance of individual buildings with existing ATES systems. In this study, it is investigated how aquifer utilization levels, obtained by varying well placement policies, affect subsurface interaction between ATES systems and how this in turn affects individual primary energy use. To this end, a building climate installation model is developed and integrated with a MODFLOW-MT3DMS thermal groundwater model. For the spatial distribution and thermal requirements of 26 unique buildings as present in the city centre of Utrecht, the placement of ATES wells is varied using an agent-based modelling approach applying dense and spacious placement restrictions. Within these simulations ATES adoption order and well placement location is randomized. Well placement density is varied for 9 scenarios by changing the distance between wells of the same and the opposite type. The results of this study show that the applied dense well placement policies lead to a 30% increase of ATES adoption and hence overall GHG emission reduction improved with maximum 60% compared to conventional heating and cooling. The primary energy use of individual ATES systems is affected at varying well placement policies by two mechanisms. Firstly, at denser well placement, ATES systems are able to place more wells, which increases the capacity of their ATES system, thereby decreasing their electricity and gas use. Secondly, aquifer utilization increases with denser well placement policies and thus interaction between individual ATES increases. At subsurface utilization up to 80%, individual primary energy use does not change significantly due to subsurface interaction. At aquifer utilization level > 80%, both negative and positive interaction is observed. Negative interaction between wells of the opposite type leads to an increase of gas or electricity use up to 15% compared to spacious well placement. On the other side, buildings may experience a maximum decrease of 15% electricity use at dense well placement due to positive interaction between wells of the same type. Local conditions like building location, plot size, distance to other buildings and heating/cooling demand determine the specific effect per building. The optimal well placement policy result from the aquifer utilisation levels discussed above. Maximum GHG emission reduction while maintaining individual ATES system performance, is achieved with well distances of 0.5–1 times the yearly average thermal radius for wells of the same type (cold-cold and warm-warm). Opposite well types (cold-warm) should be placed apart ∼2 times the thermal radius to prevent negative subsurface interaction.